2011
DOI: 10.1158/1535-7163.mct-10-0666
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Augments the Effects of Sorafenib in a Syngeneic Orthotopic Model of Hepatocellular Carcinoma

Abstract: Sorafenib targets the Raf/mitogen-activated protein kinase, VEGF, and platelet-derived growth factor pathways and prolongs survival patients in advanced hepatocellular carcinoma (HCC). Everolimus inhibits the mammalian target of rapamycin, a kinase overactive in HCC. To investigate whether the antitumor effects of these agents are additive, we compared a combined and sequential treatment regimen of everolimus and sorafenib with monotherapy. After hepatic implantation of Morris Hepatoma (MH) cells, rats were ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 31 publications
2
56
0
Order By: Relevance
“…Many lines of studies have shown that sorafenib activates the PI3K/Akt pathway (7,8,18,30), and blockage of this pathway enhances the efficacy of sorafenib (7,30), but it has also been reported that sorafenib enhances proteasome inhibitor-induced cell death by inactivating Akt in HCC (31), indicating that the complicated role of the PI3K/Akt pathway in sorafenib resistance is far from clear. Here, we have demonstrated that Akt was activated in sorafenib-resistant cells, in accordance with a previous report (9).…”
Section: Discussionmentioning
confidence: 99%
“…Many lines of studies have shown that sorafenib activates the PI3K/Akt pathway (7,8,18,30), and blockage of this pathway enhances the efficacy of sorafenib (7,30), but it has also been reported that sorafenib enhances proteasome inhibitor-induced cell death by inactivating Akt in HCC (31), indicating that the complicated role of the PI3K/Akt pathway in sorafenib resistance is far from clear. Here, we have demonstrated that Akt was activated in sorafenib-resistant cells, in accordance with a previous report (9).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K actually is partially dependent on RAS signaling (28,29). Preclinical studies have shown synergistic effects in mice with a combination of everolimus (mTOR inhibitor) and sorafenib (30). Phase I studies in renal cell and hepatocellular cancer have shown that the combination of everolimus and sorafenib was active and tolerable (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…In human HCC cell lines, everolimus, sirolimus, and temsirolimus have been shown to inhibit cell growth and proliferation [14,[16][17][18][19]. In various HCC mouse and rat models, everolimus and sirolimus significantly reduced tumor volume and angiogenesis, delayed tumor growth, and increased overall survival compared with control [16][17][18][19][20].…”
Section: Mtor Inhibitors In Hccmentioning
confidence: 99%